Modified Near-Infrared Annealing Enabled Rapid and Homogeneous Crystallization of Perovskite Films for Efficient Solar Modules - Qing Chang; Peng He; Haosong Huang; Yingchen Peng; Xiao Han; Yang Shen; Jun Yin; Zhengjing Zhao; Ye Yang; Binghui Wu; Zhiguo Zhao; Jing Li; et al. (Nano-Micro Letters)
Highlights Developing an infrared annealing system to achieve efficient annealing of perovskite films within 20 s. Fully blade-coated perovskite modules achieved remarkable efficiencies of 22.03% (6 × 6 cm2, active area: 18 cm2) and 20.18% (10 × 10 cm2, active area: 56 cm2)